2020
DOI: 10.1093/fampra/cmaa089
|View full text |Cite
|
Sign up to set email alerts
|

Team-based primary care program for disabled people and changes in rate of unmet health care needs

Abstract: Background Few studies have been conducted on the application of specific and practical methods, such as interventions, for reducing the unmet health care needs (UHCN) of disabled people. Objectives The study aims to evaluate the impact of the team-based primary care program (TPCP) for disabled people on UHCN. Method In 2017, we surveyed 696 disabled people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“… 19 A longitudinal study conducted in South Korea by Kim et al revealed a significant reduction in unmet health care needs among disabled patients following medical care provided by medical doctors and Korean medical doctors. 36 However, in our analysis, we observed that the motivation for providing HMCS among Chinese medicine practitioners was notably weaker compared to that of clinical doctors. The reasons might be complex.…”
Section: Discussionmentioning
confidence: 58%
“… 19 A longitudinal study conducted in South Korea by Kim et al revealed a significant reduction in unmet health care needs among disabled patients following medical care provided by medical doctors and Korean medical doctors. 36 However, in our analysis, we observed that the motivation for providing HMCS among Chinese medicine practitioners was notably weaker compared to that of clinical doctors. The reasons might be complex.…”
Section: Discussionmentioning
confidence: 58%
“…Despite the need for more systemic health-focused healthcare because of the high prevalence of chronic diseases and the risk of secondary functional decline that is distinct from the original disabling condition, 41 42 43 44 45 46 PWD remain doubly disadvantaged because of their lack of access to healthcare. The PHC pilot project for PWD represents major progress toward improved healthcare access and solution of unmet need for medical care 15 ; however, it is insufficient to address the unmet need for medical care among medically disadvantaged populations. Diverse institutions that provide health services for PWD should cooperate with each other; in particular, interdisciplinary cooperation, interprofessional teamwork, and community participation are key areas for success.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on the topic of the PHC pilot project for PWD, explored the experience and perception of disabled people or effectiveness of the pilot using the data only from who participated in the pilot project. 12 14 15 16 However, there is no study identified the demand for or awareness of the pilot project among the PWD living in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the Korean government has established a community program called the “Pilot Family Doctor Program for the Health of Disabilities” for two years since 2015, and the house-call satisfaction of individuals with disability has been reported to be very high [ 24 ]. Furthermore, according to the “Team-based primary care program” implemented by the “Korea Health Welfare Social Cooperative Federation” between 2015 and 2017, patients with disability reported high satisfaction with the TKM treatment and a decrease in dissatisfaction with health management [ 25 ]. Hence, the TKM health insurance needs to be promptly extended to people with disabilities.…”
Section: Discussionmentioning
confidence: 99%